EFFECT OF FIBROID IN CHANGING THE UTERINE SIZE, AND DISTORTION OF ENDOMETRIUM LINING IN A GROUP OF PRE- AND PERI-MENOPAUSAL WOMEN - Mir, Munuzza; Ameer, Saima; Alam, Zaheer; Ashraf, Maimoona; Badar, Iffat; Khurshid, Rukhshan; Azeem, Beenish; Batool, Maria (Pakistan Journal of Physiology, 2013)
Background: Knowledge of the normal dimensions of the uterus and endometrial thickening are important for evaluating the uterine health and for forecasting the risk of infertility and recurrent pregnancy loss. This study was designed to find out the effect of fibroid in changing the uterine size and distortion of endometrium lining in peri- and pre-menopausal women. Methods: Forty-six pre- and peri-menopausal women presenting to Radiology Department, Sir Ganga Ram Hospital, and Lahore General Hospital, Lahore from October 2009 to January 2010 with complaints of heavy menstrual bleeding were included in the study. A transvaginal ultrasound or pelvic ultrasound was carried out to confirm the diagnosis of fibroids and taking measurements. 5 pre and 3 peri-menopausal women with no history of any disease were taken as control. Results: Uterine size in case of both pre- and peri-menopausal woman with fibroid was non-significantly increased. Mean size of fibroid was 3.87Ã—3.84 Cm. Ultrasonography showed that the position of fibroid was either in anterior or posterior or post-fundal region in both groups of women. Mean endometrial thickness with and without fibroid was relatively same in pre-menopausol women. In peri-menopausal women endometrial thickness was slightly increased. Ultrasonography showed that fibroid pushing endometrium anterior and posterior site is more or less same but in some no effect on endometrium thickness was observed. Conclusion: Fibroid with a size of 3â€’3.5 cm cause a small change in the uterine size, distortion of endometrial lining in peri-menopausal women only. Further work is needed on large number of peri-menopausal women.